Nova Scotian Fishing Families Coping with the Fisheries Crisis - Binkley, Marian (Anthropologica, 2022)
The fisheries crisis has severely affected Nova Scotian fishing families. These fishers and their households had developed strategies to cope with the work organization and schedule of the various fisheries prosecuted in this area. Critical reductions in catches of groundfish have led to lay-offs or work reductions, to changes in work organization and to exploitation of other fisheries, some of which previously had been under utilized. This article focusses on one area of southwestern Nova Scotia to describe how new adaptations have been developed and how these previously beneficial adaptations conflict with the new situation these house holds now face.